2022
DOI: 10.1002/mlf2.12036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing global fungal threats to humans

Abstract: Fungi are an integral part of the earth's biosphere. They are broadly distributed in all continents and ecosystems and play a diversity of roles. Here, I review our current understanding of fungal threats to humans and describe the major factors that contribute to various threats. Among the 140,000 or so known species out of the estimated six million fungal species on Earth, about 10% directly or indirectly threaten human health and welfare. Major threats include mushroom poisoning, fungal allergies, infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 87 publications
(206 reference statements)
0
42
0
Order By: Relevance
“… 27 Seasonal differences have been found in many fungal pathogens, largely related to differences in temperature and moisture among seasons and the impact of those differences on fungal growth and reproduction in both our indoor and outdoor living environments. 10 , 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Seasonal differences have been found in many fungal pathogens, largely related to differences in temperature and moisture among seasons and the impact of those differences on fungal growth and reproduction in both our indoor and outdoor living environments. 10 , 32…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) is recognized as one of the most serious global threats to human health and is commonly associated with high morbidity and mortality rates and large medical cost burdens. 9 , 10 The World Health Organization (WHO) has highlighted that infections by antibiotic-resistant bacteria are responsible for around 700,000 deaths per year worldwide, if left to persist at the current rate, may lead to 10 million deaths in 2050. 11 In particular, several recent reports described increases in multidrug resistant (MDR) bacteria during the COVID-19 pandemic, with the rise in MDR bacteria rendering infections increasingly difficult to treat.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, authors should be required to submit the metadata associated with each isolate and each sequence type that they publish in their MLST study. Additional information on these STs, as well as more MLST data, especially from under-reported regions such as North America, will provide a more comprehensive understanding of the global population structure of CNSC and help develop more realistic models of global cryptococcal threat predictions and management strategies against cryptococcosis [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungi are ubiquitously distributed in both natural and anthropogenic environments, featuring a vast diversity of species, morphology, and pigmentation [ 1 , 3 , 4 ]. They can be favorable or detrimental to humans, the latter of which involves a range of mycoses, especially in immunocompromised individuals with immunological deficiency, HIV infection, and undergoing organ transplantation or cancer therapy [ 5 , 6 ]. The significant roles of fungal pigments in microbial pathogenesis have been extensively investigated and documented [ 1 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can be favorable or detrimental to humans, the latter of which involves a range of mycoses, especially in immunocompromised individuals with immunological deficiency, HIV infection, and undergoing organ transplantation or cancer therapy [ 5 , 6 ]. The significant roles of fungal pigments in microbial pathogenesis have been extensively investigated and documented [ 1 , 5 , 6 , 7 , 8 ]. Studies using fungal mutants with altered pigmentation have revealed how these pigments may provide a survival advantage for pathogens in host environments [ 8 ], for example, to aid in the evasion of the host immune system.…”
Section: Introductionmentioning
confidence: 99%